Aspek Kriminologi Terhadap Delik Pencurian yang Dilakukan Oleh Wanita Di Kota Makassar - Agnes Sutarnio (Universitas Atma jaya Makassar, 2011)
This study was aimed to examine internal and external factors causing criminal act of steal done by women in Makassar City, and its prevention effort. In the background it was explained that many steal offence done by women was essentialy caused by family economi factor. This study used descriptive methode with qualitative analysis through interview and library research, and quantitative analysis using persentage technique through frequncy tables. ...............................